Avaliação em educação infantil no município de Goiânia: um estudo documental - Valverde, Marcilene Ricarda da Silva (2022)
This paper discusses the evaluation in early childhood education of Goiânia’s Municipal Education Network, with the general purpose of aprehending the conception of evaluation in early childhood education in the interface with conceptions of child, taking into consideration the official guidelines formulated within the national and municipal scope. As specific research goals, we aim to comprehend the historical processes in the institutionalization of education of children from zero to five years old in colective environments, aprehend the conception of child from documents written by MEC, and comprehend how the evaluation conceptions are conceived in early childhood education in the city of Goiânia, based on the conception of child upon which the directives are based. In order to substantiate the research, authors such as Kramer (1982, 2001, 2014), Kramer e Leite (1996), Rosemberg (1999, 2001, 2002, 2013), Campos (1999, 2013), Kuhlmann Junior (1996, 1998, 2015), Luckesi (2005), Hoffmann (2015), Rosemberg (2001), Freitas et al. (2014), Oliveira and Cruz (2010) have been utilized. These authors collaborated with the research in the sense of comprehending the first discussions related to early childhood education, its conceptions and contradictions as an unabridged parto of basic education. The documental analysis has been based on the main national documents and on the documents produced by Goiânia’s Municipal Education Network, being analysed by means of an analysis script which contains items such as: conception of child, conception of early childhood education and conception of evaluation. The research corroborates the educational literature on the matter in the following points: in the criticism regarding the welfare conception, the defense of early childhood education prevails as a formative instance of young children in their dimensions of teaching, caring for and playing; the recurrence of a conception of child as a subject of rights, having in themself the centrality in the educational dynamics with the purpose of promoting learning and development in a wholesome perspective; the contraposition and search for overcoming the traditional, qualifying and exclusionary evaluative processes, emphasizing the reflexive, formative and mediator evanulation. However, it has been possible to identify, particularly from the Common National Curriculum Base (BNCC), a conception of education that tends to recapture early childhood education as a preparatory step for elementary school, having its axis in the preoccupation with competences and their evaluation. The main research findings reveal the presence, in the documents, of a conception of child as a subject of rights, independente and citizen. They reveal, on the other hand, the absence of a conception of evaluation in some of the analysed documents. Attention is directed to the care regarding curricular guidelines that tend to belittle the achievements related to children’s rights through a reasoning more directly linked to the imediate social interests.